1994
DOI: 10.1172/jci117282
|View full text |Cite
|
Sign up to set email alerts
|

Aminoguanidine, an inhibitor of inducible nitric oxide synthase, ameliorates experimental autoimmune encephalomyelitis in SJL mice.

Abstract: Previous work from our laboratory localized nitric oxide to the affected spinal cords of mice with experimental autoimmune encephalomyelitis, a prime model for the human disease multiple sclerosis. The present study shows that activated lymphocytes sensitized to the central nervous system encephalitogen, myelin basic protein, can induce nitric oxide production by a murine macrophage cell line. Induction was inhibited by aminoguanidine, a preferential inhibitor of the inducible nitric oxide synthase isoform, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
148
0
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(153 citation statements)
references
References 44 publications
2
148
0
3
Order By: Relevance
“…The copious amount of NO derived from this isozyme, while an important component of the armamentarium against invading pathogens (MacMicking et al 1997), accounts for much of the pathophysiology attributed to NO. This notion is supported by results from numerous studies demonstrating that selective inhibition of NOS-2 or NOS-2 gene deletion attenuates the neuropathological sequelae seen in several models of neurological diseases/ disorders (Cross et al 1994;Iadecola et al 1995;Liberatore et al 1999;MacMicking et al 1995;Nathan et al 2005;Thiemermann et al 1993). …”
mentioning
confidence: 73%
“…The copious amount of NO derived from this isozyme, while an important component of the armamentarium against invading pathogens (MacMicking et al 1997), accounts for much of the pathophysiology attributed to NO. This notion is supported by results from numerous studies demonstrating that selective inhibition of NOS-2 or NOS-2 gene deletion attenuates the neuropathological sequelae seen in several models of neurological diseases/ disorders (Cross et al 1994;Iadecola et al 1995;Liberatore et al 1999;MacMicking et al 1995;Nathan et al 2005;Thiemermann et al 1993). …”
mentioning
confidence: 73%
“…4) in the kidney, an organ that is typically not inflamed in TGF-[M -/ -mice (6,19), suggests that the increase in iNOS expression may not solely be due to the inflammatory infiltrate observed in TGF-131 -/ -mice. Two mouse models of autoimmunity, that of experimental autoimmune encephalomyelitis (29) and that of the MRL-Ipr/lpr mouse (30), are also associated with in- The role of N O in this system was to suppress the proliferation of T lymphocytes: inhibition of N O production in mice undergoing shock increased morbidity owing to increased T lymphocyte proliferation and subsequent production of TNF-ot (21).…”
Section: Resultsmentioning
confidence: 99%
“…It was proposed that the mechanism of EAE inhibition in iron-deficient mice involves the delivery and metabolism of iron for optimal CD4 þ T-cell development (Grant et al, 2003). Some investigators have shown iNOS inhibition as well as NO scavenging to suppress EAE (Cross et al, 1994;Zhao et al, 1996;Hooper et al, 1997;Jolivalt et al, 2003), whereas others have shown iNOS inhibition (O'Brien et al, 1999(O'Brien et al, , 2001 or NO donor (Xu et al, 2001) to aggravate or ameliorate EAE, thus not clarifying the exact role for NO .…”
Section: Oxidative Stress and Antioxidantsmentioning
confidence: 99%